Effect of lubricant additives on the tribological performance of aluminum anodized layers - Vasco, Marina Cardozo (2023)
Aluminum alloys are widely used in various industries due to their mechanical behavior and high strength / weight ratio, allowing for improvements in performance, fuel economy and reduced greenhouse gas emissions. However, due to their low hardness, aluminum alloys generally have limited application in situations where high wear resistance is required. Anodizing in aluminum alloys is a surface modification process that produces a high hardness alumina film that can contribute to wear reduction, positively interfering in the behavior of the tribological interface. Furthermore, the pores generated, inherent to the anodizing process, can act as reservoirs for the gradual release of lubricants in situations of wear. Anti-wear additives (AW) act by forming a protective tribofilm in the contact area. Although macro-scale studies of the AW properties of zincdialkydithiophosphates (ZDDP) have been reported in aluminum alloys, studies on the formation of ZDDP tribofilms in non-ferrous metals are relatively rare, and the possible mechanisms of tribofilm growth are still under debate. Furthermore, the addition of nanoparticles, such as nanoalumina, can further improve wear resistance in various applications. This work aimed to correlate the porosity of the anodized surface with the formation of tribofilm, contributing to the understanding of the behavior of non-metallic porous surfaces in tribological applications. For this, specimens of ALUMOLD®500, a commercial aluminum alloy of the 7xxx family, were anodized in a sulfuric acid bath at 5, 10 and 15% by volume for 30, 45 and 60 minutes, with constant current density of 45 mA/cm2, aiming at the production of anodic aluminum oxides (AAOs) of different thicknesses and porosities. These surfaces were tested in scratching and a reciprocal sphere-plane tribological configuration, with a spherical alumina counter body, in the presence of polyalphaolefin oils (PAO) with and without ZDDP. The interference of wear particles on contact were also evaluated with the addition of alumina nanoparticles under certain test conditions, to confirm an eventual positive effect of the addition of nanoparticles. Characterization of AAOs before and after testing included roughness measurements using white light interferometry, nanohardness measurements, optical microscopy, and scanning electron microscopy (SEM) images. Wear tracks and tribofilms were analyzed qualitatively by white light interferometry and SEM. It was observed that the compaction of the oxide layer increases with anodization time at concentrations of5% and 10% H2SO4 but does not behave linearly with a solution concentration of 15% H2SO4. Longer anodizing times do not produce AAO layers with greater scratch resistance, especially with increasing sulfuric acid concentration, which can be explained by the competitive growth and dissolution of AAO, inherent in the anodizing process. The addition of alumina nanoparticles to the PAO6 lubricating oil results in lower COF values, probably due to the formation of a self-laminating film, which can lead to micropolishing and can self-repair the surface, decreasing the pores of the anodized surface.